Priorities for Public Sector Research on Food Security and Natural Resources, Review 1 - Godfray, Charles (2013)
Priorities for Public Sector Research on Food Security and Natural Resources, Review 1 by Charles Godfray, Oxford University on April 12, 2013 at the Food Security Futures Conference in Dublin, Ireland.